Analisis Vonis Bebas terhadap Terdakwa Pembunuhan dalam Perspektif Keadilan Substantif (Studi Kasus Putusan Nomor 454/Pid.B/2024/PN Sby) - Putri, Brenda Saskia Delarenta (Journal Evidence Of Law, 2025)
This study aims to evaluate the verdict from the perspective of substantive justice, which emphasizes the attainment of material truth rather than merely fulfilling procedural justice. The research employs a normative legal method with statutory, conceptual, and case study approaches. The analyzed data includes court rulings, witness testimonies, forensic examination results (visum et repertum), and relevant literature on the principles of substantive justice. The discussion focuses on the contradictions between the legal facts revealed during the trial and the acquittal verdict issued by the judges. Weaknesses in assessing evidence, the application of the in dubio pro reo principle, and the disregard of the dolus eventualis concept are identified as key factors that hinder the fulfillment of substantive justice. The findings reveal that this acquittal not only neglects the rights of the victims and their families in obtaining justice but also undermines public trust in the judicial system. Overall, the decision reflects an overly formalistic approach that overlooks a thorough evaluation of the evidence and the moral consequences of the defendant's actions. Therefore, to achieve substantive justice, judicial institutions are expected to prioritize material facts and conduct more objective and comprehensive assessments in every legal decision.